Cerebrospinal Fluid BACE1 Activity and Brain Amyloid Load in Alzheimer's Disease - Timo Grimmer; Panagiotis Alexopoulos; Amalia Tsolakidou; Liang-Hao Guo; Gjermund Henriksen; Behrooz H. Yousefi; Hans Förstl; Christian Sorg; Alexander Kurz; Alexander Drzezga; Robert Perneczky (The Scientific World Journal)
The secretase BACE1 is fundamentally involved in the development of cerebral amyloid pathology in Alzheimer's disease (AD). It has not been studied so far to what extent BACE1 activity in cerebrospinal fluid (CSF) mirrors in vivo amyloid load in AD. We explored associations between CSF BACE1 activity and fibrillar amyloid pathology as measured by carbon-11-labelled Pittsburgh Compound B positron emission tomography ([11C]PIB PET). [11C]PIB and CSF studies were performed in 31 patients with AD. Voxel-based linear regression analysis revealed significant associations between CSF BACE1 activity and [11C]PIB tracer uptake in the bilateral parahippocampal region, the thalamus, and the pons. Our study provides evidence for a brain region-specific correlation between CSF BACE1 activity and in-vivo fibrillar amyloid pathology in AD. Associations were found in areas close to the brain ventricles, which may have important implications for the use of BACE1 in CSF as a marker for AD pathology and for antiamyloid treatment monitoring.